Comparison of frozen-thaw blastocyst transfer strategies in women aged 35–40 years: a retrospective study - Wu, Yanhong; Lu, Xiaosheng; Chen, Haoying; Fu, Yanghua; Zhao, Junzhao (Frontiers in Endocrinology, 2023)
Objective: To compare the effects of five different frozen-thaw embryo transfer (FET) strategies in women aged 35–40 years. Methods: Data from 1,060 patients were divided into five groups according to the number and quality of transferred blastocysts: a high-quality single blastocyst group (group A, n= 303), a high-quality double blastocysts group (group B, n= 176), a high-quality plus poor-quality double blastocysts group (group C, n= 273), a poor-quality double blastocysts group (group D, n= 189), and a poor-quality single blastocyst group (group E, n= 119). Comparative analyses were then performed between groups with regard to primary conditions, pregnancy, and neonatal outcomes. Results: Group A had the lowest twin pregnancy rate (1.97%) and incidence of low-birth-weight infants (3.45%), which were significantly different from groups B, C, and D. In addition, the preterm birth rate (7.89%), neonatal birth weight (3300 g [3000, 3637.5]), and neonatal birth age (39.14 weeks [38.43, 39.61]) in group A were different from those in groups B and C. Double blastocyst transfer (DBT) was associated with a 20.558-fold (Risk Ratio [RR]=20.558, 95% confidence interval [CI], 6.628–63.763) and 3.091-fold (RR=3.091, 95% CI, 1.69–5.653) increased risk of twin pregnancy and preterm delivery in unadjusted analysis, respectively, when compared with single blastocyst transfer (SBT). In the adjusted analysis, we observed similar risk estimates (adjusted RR=26.501, 95% CI, 8.503–82.592; adjusted RR=3.586, 95% CI, 1.899–6.769). Conclusion: Although, high-quality SBT resulted in a lower live birth rate than high-quality DBT, it also significantly reduced the risk of adverse pregnancies, thus resulting in more benefits for both the mother and baby. Collectively, our data indicate that high-quality SBT remains the optimal FET strategy for women aged 35–40 years and warrants further clinical application.